An Assessment of Skill Needs of a Sample of Iranian School Principals Based on “Successful Leaders’ Self-Development Model” - Shirbagi, Naser (Pedagogika, 2018)
The present paper is aimed at identifying Iranian principals’ needs for attributes of leadership self-development. Data collection tool was a 110-item questionnaire. The results demonstrated that there were statistically significant differences in principals’ needs level based on their demographic variables. Regarding three levels of qualities, different mean ranks were obtained. Managerial skills and attributes were in the first priority from the principal viewpoint. Among 11 leadership qualities, most of the principals expressed high need to develop their mental agility. Female principals declared more needs for developing their analytic and problem solving skills than male ones.